Ford Madox Ford’s “Cold Pastoral”: The Last Post - Reichmann, Angelika (FOCUS: Papers in English Literary and Cultural Studies, 2022)
The essay discusses the last volume of Ford Madox Ford’s tetralogy Parade’s End (1924-28). As Andrew Hampson and Robert Purssell highlight, whether The Last Post is an integral part of the tetralogy has been heavily debated since Graham Greene decided to publish the 1963 edition of the ‘Tietjens Saga’ as a trilogy. As they go on to explain, a major charge against the volume is “tying up too neatly various loose ends” (2013). Indeed, The Last Post seems to call for an interpretation in the pastoral tradition, which suggests that Ford’s novel—especially in comparison with Rebecca West’s The Return of the Soldier (1918)—ends in an idyll even if it is not free from certain ironies inherent in pastoral literature, as Seamus O’Malley (2007) maintains. In my view, on closer scrutiny, these ironies fundamentally undermine the “too neat” ending of the tetralogy. Haunted by the aftereffects of war and the ghosts of Mark’s, Christopher’s and Valentine’s former selves, dissolving identities not only by decentering but also by doubling, this apparent idyll far too often offers glimpses of its own Gothic alter ego, a narrative of madness, imprisonment and disintegration. Yet, as consistent readings of the novel in the pastoral mode imply, the Gothic double never fully takes over but, in my interpretation, subverts the superficial idyll of The Last Post, and with that, fully optimistic interpretations of the entire tetralogy.